Rāmacaritamānasa ke racanāśilpa kā viśleshaṇa - Siṃha, Yogendra Pratāpa, 1939- (Hindī Parishad Prakāśana, Ilāhābāda Viśvavidyālaya, 1981)
Study on the structure and denouement of Rāmacaritamānasa, Awadhi narrative poem on Rāma, Hindu deity, by Tulasīdāsa, 1532-1623.